Molecular Characterisation and Pathogenicity of Pasteurella Multocida Isolated In Chickens with Fowl Cholera - Man, Anun (2001)
Twenty-two isolates of Pasteurella multocida isolated from outbreaks of fowl cholera in chickens were studied. The isolates identified as Pasteurella multocida serotypes A:1, A:3 and A:1,3 based on capsular and somatic serotyping results were analysed for their DNA and protein profiles, pathogenicity and antigenicity. Genomic DNA analysis using several endonuclease enzymes by restriction endonuclease analysis (REA) and random amplified polymorphic DNA (RAPD) analysis revealed generally simil ar DNA profiles for all 22 isolates of Pasteurella multocida, except minor differences as detected upon digestion with HhaI. Molecular characterisation in the form of REA and RAPD in this study was extremely subtle to differentiate between strains of Pasteurella multocida and need further clarification along with the u5ed of these techniques. Among endonuclease enzymes used, HhaI was the only useful enzyme for differentiating strains of Pasteurella multocida. The DNA profiles obtained reflected well in serotyping and pathogenicity. This may suggests that the genetic elements encode certain virulence factors of Pasteurella multocida strains. However, there is no conclusive evidence for the role of plasmids and outer membrane protein (aMP) in the pathogenicity of Pasteurella multocida stJl'ains. All isolates that contain no plasmids and the similar aMP profiles produced difference pathogenicity among serotypes. Pathogenicity study revealed that serotype A:1,3 is more pathogenic than serotypes A:l and A:3. The rapid death and pathological changes in chicken died shortly following inoculation with pathogenic strain were considered to be indicative of shock and attributed to the action of endotoxin. The OMP analysis using SDS-PAGE revealed that all serotypes contained similar size of protein in the range of 29.0-107.0 kDa. A single major protein of 36.0 kDa, believed to be 'H' protein/porin of Pasteurella multocida was identified in all serotypes. However, there was no direct evidence to associate tlus protein with pathogenicity. The degree of aMP antigenic sharing among serotypes is extensive as revealed in immunoblotting. The 36.0 kDa protein was the most serologically major reactive antigenic protein and recognised by both homologous and heterologous antisera. Almost all antigenic proteins of serotype A:l were expressed in both serotypes A:3 and A:l,3. Results obtained may suggest that OMP of Pasteurella multocida serotype A:1 could be the potential vaccine candidate as it may share antigens that are inununologically protective.